2021
DOI: 10.7498/aps.70.20201789
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivities of different period Si/Ge superlattices

Abstract: Thermoelectric materials, which can convert wasted heat into electricity, have attracted considerable attention because they provide a solution to energy problems. The Si/Ge superlattices have shown tremendous promise as effective thermoelectric materials. The period lengths of the Si/Ge superlattices can effectively tailor the phonon's transport behaviors and control their thermal conductivities. In this paper, three kinds of Si/Ge superlattices with different period length distributions (uniform, gradient, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…MVs are important rain-producing systems in summer (May-September) in China (Zhang and Tan 2009;Xu et al 2011). Some studies have suggested that during the mei-yu season in eastern China, a series of MV activities are often seen on the mei-yu front (Fu et al 2012;Liu et al 2012;Zhang et al 2018;Fu et al 2019). Zhang et al (2018) pointed out that the long-lived MV on the mei-yu front propagating eastward is a crucial weather system that causes rainstorms in eastern China.…”
Section: Introductionmentioning
confidence: 99%
“…MVs are important rain-producing systems in summer (May-September) in China (Zhang and Tan 2009;Xu et al 2011). Some studies have suggested that during the mei-yu season in eastern China, a series of MV activities are often seen on the mei-yu front (Fu et al 2012;Liu et al 2012;Zhang et al 2018;Fu et al 2019). Zhang et al (2018) pointed out that the long-lived MV on the mei-yu front propagating eastward is a crucial weather system that causes rainstorms in eastern China.…”
Section: Introductionmentioning
confidence: 99%
“…界面声子频谱热流可以对不同结构热导率的 变化有更进一步的解释, 通过Si/Ge界面的单向光 谱热流定义为 [27,28] q(ω) 结果保持一致 [22,30] , 同时验证了模拟结果的准确 性. 随着温度的持续升高, 声子-声子散射(umklapp 过程)逐渐增强, 散射作用的增强降低了热传输 效率.…”
Section: (ω)unclassified